Peranan Sekolah Menengah Kejuruan (SMK) Pertanian Di D.I. Yogyakarta terhadap Keberlanjutan Pertanian dari Segi Sumber Daya Manusia - Ratih Ineke Wati; Muhamad Rom Ali Fikri; Roso Witjaksono (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
The one of problem in agriculture sustainability occur in the support of human resources aspect, marked by a decline in the number of people working in the agricultural sector and a decreasing in the interest of youth to work in agriculture sectors. Therefore needed for agricultural regeneration to overcome these problems. One of the institutions that play a role in agricultural regeneration is the Agricultural Vocational School. This study aims to analyze the assessment role of Agricultural Vocational Schools in DI.Yogyakarta (Special Region of Yogyakarta) towards agriculture sustainability with a variety of psychological indicators of students, This research was conducted at DI. Yogyakarta in four Agricultural Vocational Schools, using quantitative approaches and descriptive analytical basic methods. The total sample was 200 students at SMKN (Vocational School) 1 Cangkringan, SMK MM 52 Perkebunan Yogyakarta, SMKN 1 Pandak and SMKN 1 Nanggulan. The sample obtained by simple random sampling technique. The data obtained were analyzed by SEM (Structural Equation Modeling). The results of the role level analysis indicate that Agricultural Vocational Schools often play a role in the sustainability of agriculture with role level of (75.72%). SEM analysis shows that the role of Agricultural Vocational School towards agriculture sustainability has a negative effect as -0.25. Factors that influence the role of Vocational were personality reflected in motivation, perception and participation of 0.51, and school facilitation reflected in the role of the principal, teacher's role and curriculum quality of 0.45.